Philosophy of education in Belarus: problem field and prospects - Ren, Zheng (Journal of the Belarusian State University. Philosophy and Psychology, 2023)
The article identifies the origins of the philosophy of education in Belarus – the philosophical ideas of the Belarusian enlighteners, the Soviet tradition of «philosophical questions of pedagogy», the theory of Marxism, as well as the Western philosophical tradition, differing in the subject field, categorical apparatus, theoretical approaches used. The further development of the philosophy of education in the Belarus is characterised by the dominance of one of these approaches or their synthesis. The change in the political and socio-economic situation in Belarus has had a decisive impact on the very possibility of the existence of the philosophy of education, on the ideas about the problem field of the philosophy of education, the methods used and the approaches used. The following stages of the development of the philosophy of education as an academic discipline (the stage of formation (1990–2000s) and the modern stage of the development (the beginning of the 21st century – present time)) and field of research in Belarus are highlighted.
Keywords: philosophy of education; philosophical thought of Belarus; Belarusian philosophical tradition; education in Belarus; Marxism; Western philosophy of education